Uji Kualitas Bibit Kelapa Sawit dengan Pemberian Konsentrasi Biourine Kambing pada Main Nursery (Elais Guinensis Jacq) - Edward Bahar; Surya Fitri, Jenni; Lufita Nur Alfiah (Fakultas Pertanian Universitas Ratu Samban, 2024)
Riau Province has the largest oil palm plantation area in Indonesia, reaching 2,594,227 ha. One of the main challenges in oil palm cultivation is to increase seedling productivity through the provision of optimal nutrients. This study aims to evaluate the effect of goat biourine as liquid organic fertilizer on the growth of oil palm seedlings (Elaeis guineensis Jacq.) in the main nursery and determine the best biourine concentration. The research was conducted in a completely randomized design (CRD) consisting of five treatments of goat biourine concentration (0, 200, 300, 400, and 500 ml/liter of water) with three replications, resulting in 15 experimental units. The observed variables included biourine nutrient content analysis, seedling height, midrib length, midrib number, and culm diameter. The results showed that the application of goat biourine had a significant effect on midrib length at a concentration of 400 ml/liter of water, but had no significant effect on seedling height, number of midribs, and cob diameter. Goat biourine is proven as an alternative organic fertilizer that can support the growth of oil palm seedlings, but further research is needed to explore the optimal dose and higher nutrient content, especially nitrogen, to increase efficacy.